Musical imaginations multidisciplinary perspectives on creativity, performance and perception - Hargreaves, David J. (David John), 1948-; Miell, Dorothy; MacDonald, Raymond A. R. (Oxford : Oxford University Press, 2012)
Musical imagination and creativity are amongst the most abstract and complex aspects of musical behaviour. This book is a wide ranging, multidisciplinary review of the latest theory and research on musical creativity, performance and perception by some of the most eminent scholars in their respective disciplines.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Includes bibliographical references and index.
Keywords: Music -- Psychological aspects; Creative ability; Imagination